Heat-evolved microalgal symbionts increase thermal bleaching tolerance of coral juveniles without a trade-off against growth - Kate M. Quigley; Carlos Alvarez-Roa; Jean-Baptiste Raina; Mathieu Pernice; Madeleine J. H. van Oppen (Coral Reefs, 2023)
Global climate change is threatening the persistence of coral reefs as associated summer heatwaves trigger the loss of microalgal endosymbionts (Symbiodiniaceae) from the coral tissues, or coral bleaching. We infected aposymbiotic juveniles of the coral Acropora tenuis with either wildtype (WT10) or heat-evolved (SS1 or SS8) Symbiodiniaceae strains Cladocopium proliferum (formerly referred to as Cladocopium goreaui and Cladocopium C1 acro ). After 10 months at 27 °C, SS8-juveniles were 2 × larger than SS1- or WT10-juveniles. In response to a simulated heatwave (31 °C for 41 days), the WT10-juveniles bleached and showed a decline in respiration while cell densities and respiration in both SS-juvenile groups remained unchanged compared to the controls. These results reveal that some heat-evolved strains can increase the bleaching tolerance of juvenile corals without a trade-off against growth. This response is opposite to the lower nutrient provisioning often reported for naturally thermotolerant Symbiodiniaceae (e.g. genus Durusdinium ) , thereby offering enhanced fitness to the host without the ecological consequences of diminished growth.

First outdoor cultivation of the N2-fixing cyanobacterium Tolypothrix sp. in low-cost suspension and biofilm systems in tropical Australia - Chinnathambi Velu; Samuel Cirés; Carlos Alvarez-Roa; Kirsten Heimann (Journal of Applied Phycology, 2015)